Chování městských a vesnických dětí v mladším školním věku - Světlíková, Hana; Škvařilová, Božena (Lidé města, 2006)
The study was oriented at the evaluation of the complex behavioural expression of children with the help of six selected components of nonverbal communication (mobility, social cooperation, distance from the nearest child, eye contact, acoustic communication, intensity of acoustic communication and hands behaviour) and their influence by certain biological and social factors (place and age).